Analisis Berpikir Fungsional Siswa SMP dalam Generalisasi Pola Ditinjau dari Gaya Kognitif - Taufik, Abdul Rachman; Mayasari, Dita; Natsir, Irmawanty; Dadi, Oswaldus (JRPM (Jurnal Review Pembelajaran Matematika), 2023)
This study focuses on the functional thinking activities of students in solving the task of generalization of patterns in terms of cognitive style. The research subjects consisted of 2 junior high school students in grade VIII consisting of one student with a field-dependent cognitive style and one student with a field-independent cognitive style determined by using the GEFT instrument. An interview based on a pattern generalization test was used to collect data on students' functional thinking. The results showed that at the stage of identifying patterns, both subjects used symbol representation in identifying patterns. At the stage of determining the relationship between two quantities, Field Independent uses trial and error rules to determine the relationship between two quantities, while Field Dependent lists all terms to determine the relationship between two quantities. At the stage of determining the general rule, Field Independent identifies the regularity of the pattern from the results of the relationship between two quantities, while Field Dependent determines the general rule by identifying the difference between two adjacent terms and then summing with the term in question.